Liquid crystal polyester film, metal-laminated film made using the film, and circuit board

JP2025026355APending Publication Date: 2025-02-21OKURA INDUSTRIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024117863
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-07-23
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0013】 本発明では、結晶化温度付近の動摩擦係数が小さく、また結晶化温度付近の動摩擦係数の変化が小さい、弛みやシワのない平滑な液晶ポリエステル系フィルムを得ることができる。また、本発明の液晶ポリエステル系フィルムは、機械的特性、電気的特性、耐熱性に優れるとともに、フィルムの平滑性に優れ得ることから厚みの均一性にも優れ、液晶ポリエステル系フィルムと金属層とを貼り合わせて得られる金属ラミネートフィルムは、優れた機械的特性、電気的特性、はんだリフロー性を備えるとともに、高周波数帯域の信号伝送の挿入損失が小さく、高速通信用途に適した回路基板用の積層板等の用途に好適に使用することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026355000001_ABST
    Figure 2025026355000001_ABST
Patent Text Reader

Abstract

To provide a liquid crystal polyester film that exhibits excellent mechanical properties, electrical properties, and heat resistance, while ensuring a smooth surface with controlled film sagging and wrinkling during extrusion molding, such as inflation extrusion molding.SOLUTION: A liquid crystal polyester film contains thermoplastic liquid crystal polyester as a main component, where the crystallization temperature (Tc) is 180°C or more and 320°C or less, and the dynamic friction coefficient (μD1) at the crystallization temperature Tc+5°C is 0.25 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polyester film containing as a main component a thermoplastic liquid crystal polyester capable of forming an optically anisotropic molten phase, and to a metal laminate film and a circuit board using said film. [Background technology]

[0002] In recent years, there has been a growing demand in the electronics and electrical fields for smaller and lighter devices, and insulating films with excellent electrical and mechanical properties are in demand. However, conventional raw materials for insulating films, such as polyimide and polyethylene terephthalate, have insufficient electrical properties in the high frequency range, and are highly hygroscopic, which can lead to poor electrical properties and large dimensional changes, making it difficult to create films that meet the above requirements.

[0003] Thermoplastic liquid crystal polyester has been attracting attention as a material for flexible printed circuit (FPC) boards and other devices due to its excellent mechanical properties such as heat resistance and rigidity, chemical resistance, and dimensional accuracy, as well as its excellent electrical properties (low dielectric constant, low dielectric tangent) in the high frequency range (GHz band) and low transmission loss in circuits.

[0004] Thermoplastic liquid crystal polyester can be formed into a film by various extrusion molding methods. However, a film formed by a T-die extrusion molding method shows anisotropy in the molecular chain orientation in the take-up direction (MD direction) and the direction perpendicular thereto (TD direction) because the thermoplastic liquid crystal polyester has a rigid molecular structure and the molecules tend to be oriented in the flow direction in a molten state, making it difficult to obtain a thermoplastic liquid crystal polyester film with isotropic molecular chain orientation.

[0005] In contrast, in the inflation extrusion molding method, since the molten thermoplastic liquid crystal polyester extruded from the annular die can be stretched in two directions, MD and TD, it is easy to obtain an isotropic thermoplastic liquid crystal polyester film by appropriately adjusting the blow ratio and controlling the orientation of the molecular chain. For this reason, various studies using the inflation extrusion molding method have been conducted in the production of a thermoplastic liquid crystal polyester film. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2001-88213 [Patent Document 2] Patent Publication No. 2002-240146 Summary of the Invention [Problem to be solved by the invention]

[0007] However, thermoplastic liquid crystal polyesters have a high tensile modulus and a small elongation at break, and therefore have high rigidity. When produced into a film by inflation extrusion molding, the film tends to wrinkle and sag, making it difficult to obtain a smooth film.

[0008] For example, in the inflation extrusion method, molten resin is extruded from an annular slit into a bubble shape, and air or inert gas is blown into the inside of the bubble made of the molten resin to expand and stretch the bubble in the MD and TD directions. The expanded and stretched bubble is gradually folded flat while being brought into contact with a pair of stabilizers that are inclined so that the downstream sides in the MD direction are close to each other, and is guided to pinch rolls, where the bubble is folded flat by the pair of pinch rolls. However, in the process of folding a cylindrical bubble flat while being brought into contact with the stabilizer plates and folding it flat by the pinch rolls, the bubble located at the center of the stabilizer plates and the bubbles located at both ends of the stabilizer plates have geometrically different linear distances from the position where the bubble directly contacts the stabilizer plates to the pinch rolls. Therefore, if the resin is highly rigid, the film cannot deform when it is nipped flat between the pinch rolls, and sagging and wrinkles in the MD direction (vertical wrinkles) occur in the film.

[0009] For this reason, when forming a film from a thermoplastic liquid crystal polyester by inflation extrusion molding, it is effective to control the resin temperature of the bubble when folding the bubble into a flat shape between pinch rolls to a relatively high temperature so that the film is easily deformed when nipped while maintaining the shape of the bubble, thereby suppressing the occurrence of slackness and vertical wrinkles in the film. On the other hand, if the resin temperature of the bubble is controlled to a relatively high temperature up to the pinch roll position, the sliding property of the bubble deteriorates, and crescent-shaped wrinkles (horizontal wrinkles) occur in the TD direction of the bubble due to friction between the bubble and the stabilizer, resulting in a new problem that it is difficult to obtain a smooth film.

[0010] The present invention has been made in consideration of such problems, and aims to provide a smooth liquid crystal polyester film that has excellent mechanical properties, electrical properties, and heat resistance, and in which sagging and wrinkles of the film are controlled during extrusion molding such as inflation extrusion molding. [Means for solving the problem]

[0011] The present inventors have intensively studied smooth liquid crystal polyester films that are excellent in mechanical properties, electrical properties, and heat resistance, and that are controlled in loosening and wrinkles during extrusion molding such as inflation extrusion molding. As a result, they have focused on the sliding properties of the film near the crystallization temperature at which the molecular chains of the thermoplastic liquid crystal polyester in a molten state form an oriented state, and have found that the sliding properties of the thermoplastic liquid crystal polyester change significantly near the crystallization temperature, and the sliding properties deteriorate.The present inventors have found that by controlling the sliding properties of the film near the crystallization temperature, it is possible to obtain a smooth liquid crystal polyester film that is suppressed in loosening and wrinkles during extrusion molding such as inflation extrusion molding, and have completed the present invention.

[0012] According to the present invention, (1) A liquid crystal polyester-based film containing a thermoplastic liquid crystal polyester as a main component, the crystallization temperature (Tc) is 180°C or more and 320°C or less, and the dynamic friction coefficient (μ D1 A liquid crystal polyester film is provided, characterized in that the ratio of the thickness of the liquid crystal layer to the thickness of the liquid crystal layer is 0.25 or less, (2) A liquid crystal polyester-based film containing a thermoplastic liquid crystal polyester as a main component, the crystallization temperature (Tc) is 180°C or more and 320°C or less, and the dynamic friction coefficient (μ D1 ) and the dynamic friction coefficient (μ D2 ) and the dynamic friction coefficient ratio (μ D1 / μ D2 ) is 1.25 or less, (3) The liquid crystal polyester film according to (1) or (2) is provided, characterized in that the thermoplastic liquid crystal polyester contains at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid; (4) The liquid crystal polyester film according to (1) or (2), characterized in that the crystallization temperature (Tc) is 220° C. or higher and 300° C. or lower, (5) The liquid crystal polyester film according to (1) or (2) is provided, which comprises an amorphous copolyester having a glass transition temperature of 80° C. or more and 200° C. or less, (6) The liquid crystal polyester film according to (5) is provided, characterized in that the amorphous copolyester contains a structural unit derived from a terephthalic acid monomer and a structural unit derived from 1,4-cyclohexanedimethanol; (7) The liquid crystal polyester film according to (1) or (2) is provided, which is an inflation film, (8) A metal laminate film is provided, characterized in that a metal layer is laminated on one or both sides of the liquid crystal polyester film according to (1) or (2), (9) There is provided a circuit board comprising at least one conductor layer and the liquid crystal polyester film according to (1) or (2). Effect of the Invention

[0013] In the present invention, a smooth liquid crystal polyester film can be obtained that has a small dynamic friction coefficient near the crystallization temperature, a small change in the dynamic friction coefficient near the crystallization temperature, and is free from slackness and wrinkles.The liquid crystal polyester film of the present invention is excellent in mechanical properties, electrical properties, and heat resistance, and can have excellent film smoothness, so that it is also excellent in thickness uniformity.The metal laminate film obtained by bonding the liquid crystal polyester film and a metal layer has excellent mechanical properties, electrical properties, and solder reflow properties, and has small insertion loss in high-frequency band signal transmission, and can be suitably used for applications such as laminates for circuit boards suitable for high-speed communication applications. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic diagram showing an example of a measuring device for measuring a dynamic friction coefficient in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and various embodiments can be made within the scope of the effects of the present invention.

[0016] [Liquid crystal polyester film] The liquid crystal polyester film of the present invention contains a thermoplastic liquid crystal polyester as a main component, and is characterized by excellent sliding properties around the crystallization temperature. Specifically, in one embodiment, the dynamic friction coefficient (μ D1 ) is 0.25 or less. The liquid crystal polyester film having such characteristics has a small dynamic friction coefficient near the crystallization temperature, and therefore has excellent sliding properties with the stabilizer plate in extrusion molding such as inflation extrusion molding, and a smooth film without slack or wrinkles can be obtained. In addition, when the dynamic friction coefficient is small near the crystallization temperature, the occurrence of wrinkles can be suppressed when the liquid crystal polyester film and the metal foil are heat-pressed (laminated) using a heating roll or the like, and a smooth metal laminate film can be obtained. Here, the main component means that the composition ratio of the components constituting the film is 50% by weight or more, preferably 60% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0017] Dynamic friction coefficient (μ D1 ) is preferably 0.24 or less, more preferably 0.23 or less, even more preferably 0.22 or less, and particularly preferably 0.20 or less. D1 The lower limit of the dynamic friction coefficient (μ) is not particularly limited, but is, for example, 0.01 or more, preferably 0.03 or more, and more preferably 0.05 or more. D1The method for obtaining a liquid crystal polyester film having a coefficient of dynamic friction (μ) that satisfies the above range is not particularly limited, but examples thereof include adjusting the type of monomer component of the thermoplastic liquid crystal polyester, the molar ratio of the monomer component, the degree of polymerization, etc., blending two or more types of thermoplastic liquid crystal polyester having different compositions, blending an amorphous polymer, and blending particles made of an inorganic material or an organic material that improves sliding properties. D1 ) can be measured according to JIS K7125 by the method described below.

[0018] In another embodiment, the liquid crystal polyester film of the present invention has a dynamic friction coefficient (μ D1 ) and the dynamic friction coefficient (μ D2 ) and the dynamic friction coefficient ratio (μ D1 / μ D2 ) is 1.25 or less. A liquid crystal polyester film having such characteristics has a small increase and small change in the dynamic friction coefficient near the crystallization temperature, so that in extrusion molding such as inflation extrusion molding, the process window for film formation is wide, the sliding property with the stabilizer plate is excellent, and a smooth film without slack or wrinkles can be obtained. In addition, if the increase in the dynamic friction coefficient near the crystallization temperature is small, the occurrence of wrinkles can be suppressed when the liquid crystal polyester film and metal foil are hot-pressed (laminated) using a heating roll or the like, and a smooth metal laminate film can be obtained. The dynamic friction coefficient ratio (μ D1 / μ D2 ) is preferably 1.20 or less, more preferably 1.15 or less, even more preferably 1.10 or less, and particularly preferably 1.00 or less. D1 / μ D2 The lower limit of the dynamic friction coefficient ratio (μ) is not particularly limited, but is, for example, 0.01 or more, preferably 0.03 or more, and more preferably 0.05 or more. D1 / μ D2The method for obtaining a liquid crystal polyester film having a kinetic friction coefficient (μ) that satisfies the above range is not particularly limited, but examples thereof include adjusting the type of monomer component of the thermoplastic liquid crystal polyester, the molar ratio of the monomer component, the degree of polymerization, etc., blending two or more types of thermoplastic liquid crystal polyesters having different compositions, blending an amorphous polymer, and blending particles made of an inorganic material or an organic material that improves sliding properties. D1 , μ D2 ) can be measured according to JIS K7125 by the method described below.

[0019] The crystallization temperature (Tc) of the liquid crystal polyester film of the present invention is 180°C or more and 320°C or less. If the crystallization temperature (Tc) is in the above range, a smooth film having excellent mechanical properties, electrical properties, and heat resistance, excellent moldability, and no loosening or wrinkles can be obtained. The upper limit of the crystallization temperature (Tc) is preferably 310°C or less, more preferably 300°C or less, even more preferably 295°C or less, and particularly preferably 290°C or less. The lower limit of the crystallization temperature (Tc) is preferably 190°C or more, more preferably 200°C or more, even more preferably 210°C or more, and particularly preferably 220°C or more. The crystallization temperature (Tc) of the liquid crystal polyester film is a value measured by a differential scanning calorimeter (DSC). Specifically, the liquid crystal polyester film is heated from room temperature to 320 to 380°C at a heating rate of 10°C / min to completely melt the film, and then cooled to 30°C at a cooling rate of 10°C / min. The apex of the exothermic peak obtained when the film is cooled is defined as the crystallization temperature (Tc).

[0020] The thickness of the liquid crystal polyester film of the present invention is not particularly limited, but is, for example, 0.5 μm or more and 1000 μm or less. Taking into consideration the handleability and productivity of the film, it is preferably 5 μm or more and 500 μm or less, more preferably 10 μm or more and 300 μm or less, and even more preferably 20 μm or more and 200 μm or less.

[0021] The liquid crystal polyester film of the present invention preferably has a tensile strength of 180 MPa or more in the machine direction (MD direction) and the width direction (TD direction). The tensile strength is more preferably 200 MPa or more, and even more preferably 220 MPa or more. The upper limit of the tensile strength is not particularly limited, but is preferably, for example, 500 MPa or less, more preferably 400 MPa or less, and even more preferably 350 MPa or less. If the tensile strength is within the above range, the film has excellent handleability when processed into a laminate for a circuit board suitable for high-speed communication applications, and can suppress defects and cracks that occur at the ends of the film.

[0022] The liquid crystal polyester film of the present invention preferably has low anisotropy in the machine direction (MD) and width direction (TD). In particular, the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the machine direction of the film (i.e., F(TD) / F(MD)) is preferably 0.5 to 1.5, more preferably 0.75 to 1.25, even more preferably 0.85 to 1.15, and particularly preferably 0.90 to 1.10. If the tensile strength F(TD) in the width direction of the film relative to the tensile strength F(MD) in the machine direction of the film is within the above range, the anisotropy of the mechanical and electrical properties of the film is small, and it can be suitably used for applications such as laminates for circuit boards suitable for high-speed communication applications.

[0023] The liquid crystal polyester film of the present invention preferably has a dielectric loss tangent of 0.0025 or less, more preferably 0.0024 or less, even more preferably 0.0022 or less, and particularly preferably 0.0020 or less. The liquid crystal polyester film of the present invention preferably has a relative dielectric constant of 2.0 to 4.0. The relative dielectric constant is more preferably 2.5 to 3.9, more preferably 2.6 to 3.8, and even more preferably 2.8 to 3.8. The dielectric properties including the standard dielectric loss tangent and the relative dielectric constant can be measured by a cavity resonator perturbation method.

[0024] [Thermoplastic liquid crystal polyester] The thermoplastic liquid crystal polyester used in the present invention is a liquid crystal polyester exhibiting melt anisotropy (a polyester capable of forming an optically anisotropic melt phase). The melt anisotropy can be confirmed by a conventional polarized light inspection method using crossed polarizers. Specifically, the melt anisotropy can be confirmed by using a polarizing microscope (manufactured by Olympus Corporation, etc.) to melt a sample placed on a hot stage (manufactured by Linkam Co., Ltd., etc.) and observing it at a magnification of 150 times under a nitrogen atmosphere. A liquid crystal resin that exhibits optical anisotropy when melted is optically anisotropic and transmits light when inserted between crossed polarizers. If the sample is optically anisotropic, polarized light will transmit even when it is in a molten, stationary liquid state, for example.

[0025] The thermoplastic liquid crystal polyester is not particularly limited in terms of its chemical composition as long as it is a liquid crystal polyester that can be melt-molded, and examples thereof include thermoplastic liquid crystal polyesters having a repeating unit derived from at least one selected from the group consisting of aromatic hydroxycarboxylic acids, aromatic or aliphatic diols, aromatic or aliphatic dicarboxylic acids, aromatic diamines, aromatic hydroxyamines, and aromatic aminocarboxylic acids.

[0026] Examples of aromatic hydroxycarboxylic acids include p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, and 4-(4-hydroxyphenyl)benzoic acid. These compounds may have a substituent such as a halogen atom, a lower alkyl group, and a phenyl group. Among them, p-hydroxybenzoic acid or 6-hydroxy-2-naphthoic acid is preferred. Examples of aromatic or aliphatic diols include aromatic diols. Examples of aromatic diols include hydroquinone, 4,4'-dihydroxybiphenyl, 3,3'-dimethyl-1,1'-biphenyl-4,4'-diol, and acylated products thereof, with hydroquinone or 4,4'-dihydroxybiphenyl being preferred. Examples of aromatic or aliphatic dicarboxylic acids include aromatic dicarboxylic acids. Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid, with terephthalic acid being preferred. Examples of aromatic diamines, aromatic hydroxyamines, and aromatic aminocarboxylic acids include p-phenylenediamine, 4-aminophenol, and 4-aminobenzoic acid.

[0027] The thermoplastic liquid crystal polyester preferably has at least one repeating unit selected from the group consisting of repeating units represented by the following formulas (1) to (3). -O-Ar1-CO-(1) -CO-Ar2-CO-(2) -X-Ar3-Y-(3) In formula (1), Ar1 represents a phenylene group, a naphthylene group, or a biphenylene group. In formula (2), Ar2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group represented by the following formula (4). In formula (3), Ar3 represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4), and X and Y each independently represent an oxygen atom or an imino group. -Ar4-Z-Ar5-(4) In formula (4), Ar4 and Ar5 each independently represent a phenylene group or a naphthylene group, and Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group, or an alkylene group. The phenylene group, the naphthylene group and the biphenylene group may have a substituent selected from the group consisting of a halogen atom, an alkyl group and an aryl group.

[0028] In particular, the thermoplastic liquid crystal polyester preferably has at least one repeating unit selected from the group consisting of a repeating unit derived from an aromatic hydroxycarboxylic acid represented by the above formula (1), a repeating unit derived from an aromatic diol represented by the above formula (3) in which X and Y are both oxygen atoms, and a repeating unit derived from an aromatic dicarboxylic acid represented by the above formula (2).

[0029] In addition, the thermoplastic liquid crystal polyester preferably has a structural unit derived from an aromatic hydroxycarboxylic acid, more preferably has at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid, and even more preferably has a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid.

[0030] In another preferred embodiment, the thermoplastic liquid crystal polyester preferably has at least one selected from the group consisting of a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from an aromatic diol, a structural unit derived from terephthalic acid, and a structural unit derived from 2,6-naphthalenedicarboxylic acid, and more preferably has all of a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from an aromatic diol, a structural unit derived from terephthalic acid, and a structural unit derived from 2,6-naphthalenedicarboxylic acid.

[0031] The synthesis method of the thermoplastic liquid crystal polyester is not particularly limited, and the above compound can be synthesized by polymerizing it by a known method such as melt polymerization, solid phase polymerization, solution polymerization, and slurry polymerization. As the thermoplastic liquid crystal polyester, a commercially available product may be used. Examples of commercially available thermoplastic liquid crystal polyester include "LAPEROS" manufactured by Polyplastics Co., Ltd., "VECTRA" manufactured by Celanese Co., Ltd., "UENO LCP" manufactured by Ueno Pharmaceutical Co., Ltd., "SUMIKA SUPER LCP" manufactured by Sumitomo Chemical Co., Ltd., "ZYDAR" manufactured by ENEOS Corporation, and "SIVELAS" manufactured by Toray Industries, Inc. In addition, the thermoplastic liquid crystal polyester may form a chemical bond with an optional component such as a crosslinking agent or a compatible component (reactive compatibilizer).

[0032] The melting point (Tm) of the thermoplastic liquid crystal polyester is preferably 250°C or higher. If the melting point is lower than 250°C, the solder reflow property is poor, so that when used for applications such as printed circuit boards, the processing method is limited. The melting point of the thermoplastic liquid crystal polyester is not particularly limited, but from the viewpoint of heat resistance and moldability, it is preferably 400°C or lower, more preferably 350°C or lower, even more preferably 330°C or lower, and particularly preferably 300°C or lower. The lower limit of the melting point is more preferably 260°C or higher, and even more preferably 270°C or higher. The melting point of the thermoplastic liquid crystal polyester can be measured by a conventionally known method, for example, a differential scanning calorimeter (DSC) is used to heat a sample at a heating rate of 10°C / min to completely melt it, and then the melt is cooled to 30°C at a heating rate of 10°C / min, and the melt is heated again at a heating rate of 10°C / min. The apex of the endothermic peak that appears when this is taken as the melting point.

[0033] [Amorphous copolyester] In a preferred embodiment, the liquid crystal polyester film of the present invention may contain an amorphous copolyester in addition to the thermoplastic liquid crystal polyester. A liquid crystal polyester film containing an amorphous copolyester in addition to the thermoplastic liquid crystal polyester has excellent sliding properties near the crystallization temperature. The amorphous copolyester is a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol, and does not have a clear endothermic peak in thermal analysis measurement using differential scanning calorimetry (DSC). For example, in thermal analysis measurement using DSC, it has only a stepwise endothermic change, is a solid at room temperature, and is thermally plasticized at a temperature above the glass transition temperature.

[0034] The amorphous copolyester preferably contains a structural unit derived from a terephthalic acid monomer and a structural unit derived from 1,4-cyclohexanedimethanol. The terephthalic acid monomer is terephthalic acid or a derivative of terephthalic acid. Examples of the derivative of terephthalic acid include halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides, and mixtures thereof of terephthalic acid. Examples of the derivative of terephthalic acid include dialkyl esters and diaryl esters of terephthalic acid, and specific examples thereof include dimethyl terephthalate (DMT) and diethyl terephthalate.

[0035] The amorphous copolyester may further contain a constituent unit derived from another monomer. In one embodiment, the amorphous copolyester further contains a constituent unit derived from a dicarboxylic acid (other dicarboxylic acid) other than a terephthalic acid monomer. Examples of the other dicarboxylic acid include cyclohexanedicarboxylic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, and stilbene dicarboxylic acid. Examples of the cyclohexanedicarboxylic acid include 1,3- and / or 1,4-cyclohexanedicarboxylic acid. When the amorphous copolyester contains a constituent unit derived from another dicarboxylic acid, the content of the constituent unit derived from a terephthalic acid monomer is preferably 40 mol% or more, more preferably 40 mol% to 90 mol%, and even more preferably 50 mol% to 85 mol% based on the total amount of dicarboxylic acid (the total amount of the constituent units derived from a terephthalic acid monomer and the constituent units derived from the other dicarboxylic acid).

[0036] The amorphous copolyester may further contain a constituent unit derived from a diol other than 1,4-cyclohexanedimethanol (another diol). Examples of the other diol include aliphatic or alicyclic glycols (preferably having 2 to 20 carbon atoms). Examples of the other diol include ethylene glycol, diethylene glycol, triethylene glycol, propanediol, butanediol, pentanediol, hexanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and the like. In one embodiment, the amorphous copolyester further contains a constituent unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol. When the amorphous copolyester contains a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), the content of the structural unit derived from 1,4-cyclohexanedimethanol (CHDM) is preferably 10 mol% to 90 mol%, more preferably 20 mol% to 85 mol%, and even more preferably 30 mol% to 80 mol%, based on the total of the structural units derived from TMCD and the structural units derived from CHDM. The content of the structural units derived from TMCD is preferably 10 mol% to 90 mol%, more preferably 15 mol% to 80 mol%, and even more preferably 20 mol% to 70 mol%, based on the total of the structural units derived from TMCD and the structural units derived from CHDM.

[0037] The glass transition temperature (Tg) of the amorphous copolyester is 80° C. or more and 200° C. or less, preferably 85° C. or more and 180° C. or less, more preferably 90° C. or more and 160° C. or less, even more preferably 95° C. or more and 150° C. or less, and particularly preferably 100° C. or more and 140° C. or less. The glass transition temperature can be measured by a conventionally known method, for example, by differential scanning calorimetry in accordance with JIS K-7121:2012. In addition, when the manufacturer has a published value for the glass transition temperature, the published value by the manufacturer may be used.

[0038] When the liquid crystal polyester film of the present invention contains an amorphous copolyester, the blending ratio of the thermoplastic liquid crystal polyester (A) and the amorphous copolyester (B) is preferably (A):(B)=50-99.5% by weight:0.5-50% by weight. More preferably, (A):(B)=70-99% by weight:1-30% by weight, even more preferably, (A):(B)=85-98% by weight:2-15% by weight, and particularly preferably, (A):(B)=90-97.5% by weight:2.5-10% by weight. If the blending amount of the amorphous copolyester is less than the above range, the effect of improving the sliding property near the crystallization temperature of the liquid crystal polyester film is poor, and it may be difficult to obtain a smooth film by film forming processing of the film by the inflation extrusion molding method. If the blending amount of the amorphous copolyester is more than the above range, the heat resistance and mechanical properties of the liquid crystal polyester film may be reduced.

[0039] The liquid crystal polyester film of the present invention may contain other resin components other than the above-mentioned thermoplastic liquid crystal polyester and amorphous copolyester within the range that does not impair the effects of the present invention. Examples of other resin components include thermoplastic resins such as polyarylate, polyphenylene sulfide, polyphenylene ether, polyether ether ketone, polyetherimide, cycloolefin polymer, polyamide, polyamideimide, polyimide, epoxy group-containing olefin copolymer, styrene resin, and copolyester elastomer. In addition, the liquid crystal polyester film of the present invention may contain additives such as a compatibilizer, a lubricant, and an antioxidant.

[0040] The liquid crystal polyester film of the present invention may contain inorganic particles and organic particles as a reinforcing material, a matting material, a dielectric constant / dielectric tangent improving material, and a sliding property improving material. Examples of inorganic particles include silica, titanium oxide, barium sulfate, talc, zirconia, alumina, silicon nitride, silicon carbide, calcium carbonate, silicate, glass beads, graphite, tungsten carbide, carbon black, clay, mica, carbon fiber, glass fiber, and metal powder. Examples of organic particles include crosslinked acrylic beads and crosslinked styrene beads. The content of inorganic particles and organic particles is 0 to 40% by weight based on the total mass of the liquid crystal polyester film.

[0041] [Method of manufacturing liquid crystal polyester film] The method for producing the liquid crystal polyester film of the present invention is not particularly limited as long as it is a method capable of producing a smooth film without slack or wrinkles, but it is preferable that the film is an inflation film produced by an inflation extrusion molding method.

[0042] When the components constituting the liquid crystal polyester film include other components such as thermoplastic liquid crystal polyester and amorphous copolyester, it is preferable to melt-knead and granulate the components prior to film formation in order to provide a stable kneaded state.The equipment for melt-kneading is not particularly limited, and examples thereof include various known extruders such as batch kneaders, kneaders, co-kneaders, Banbury mixers, roll mills, single-screw or twin-screw extruders.Among these, single-screw extruders and twin-screw extruders are preferably used because of their excellent kneading ability and productivity.

[0043] An example of the inflation extrusion molding is a method in which the above-mentioned resin composition is fed to a melt extruder equipped with a die having an annular slit, the molten resin composition is extruded upward or downward in a bubble shape from the annular slit of the extruder, and air or an inert gas is blown into the bubble of the molten resin composition from inside to expand and stretch the bubble in a direction (TD) perpendicular to the flow direction (MD) to obtain a film. The cylinder temperature of the melt extruder is usually 260 to 400°C, preferably 280 to 380°C. The interval of the annular slit is usually 0.1 to 5 mm, preferably 0.2 to 2 mm. The diameter of the annular slit is usually 20 to 1000 mm, preferably 25 to 600 mm.

[0044] In inflation extrusion molding, the blow ratio is preferably 1.5 or more, more preferably 2.0 or more, even more preferably 4.0 or more, and particularly preferably 4.5 or more. The upper limit of the blow ratio is not particularly limited, but for example, the blow ratio is 10 or less. The draft ratio is preferably 1.5 to 20, more preferably 1.5 to 10. Here, the blow ratio is the stretch ratio in the TD direction, and the draft ratio is the stretch ratio in the MD direction. When the blow ratio and the draft ratio are within the above ranges, the anisotropy of the tensile modulus and tensile strength of the obtained film (difference between the MD direction and the TD direction) can be improved.

[0045] The liquid crystal polyester film of the present invention can be further subjected to a heat treatment to relax the orientation of the molecular chains and improve the film dimensional stability. The heat treatment can be a conventionally known method, for example, a contact heat treatment, a non-contact heat treatment, etc., and the type is not particularly limited.

[0046] [Metal laminate film] The liquid crystal polyester film of the present invention may be used as a metal laminate film by laminating a metal layer thereon. When laminating the metal layer, the surface of the liquid crystal polyester film on which the metal layer is to be laminated may be subjected to corona discharge treatment, ultraviolet irradiation treatment or plasma treatment in order to increase adhesive strength.

[0047] Examples of the method for laminating a metal layer on the liquid crystal polyester film of the present invention include (1) a method for attaching a liquid crystal polyester film to a metal foil by heat and pressure bonding, (2) a method for attaching a liquid crystal polyester film and a metal foil with an adhesive, and (3) a method for forming a metal layer on a liquid crystal polyester film by vapor deposition. Among them, the lamination method (1) is a method for pressing the liquid crystal polyester film to a metal foil at a temperature near the flow start temperature of the liquid crystal polyester film using a press or a heated roll, and is recommended because it can be easily performed. Examples of the adhesive used in the lamination method (2) include hot melt adhesives and polyurethane adhesives. Among them, epoxy group-containing ethylene copolymers are preferably used as adhesives. Examples of the lamination method (3) include ion beam sputtering, high frequency sputtering, direct current magnetron sputtering, and glow discharge. Among them, high frequency sputtering is preferably used.

[0048] Examples of metals used in the metal layer include gold, silver, copper, copper alloys, nickel, nickel alloys, aluminum, aluminum alloys, iron, and iron alloys. Copper is preferred for tab tapes and circuit boards, and aluminum is preferred for capacitors. Examples of the structure of the metal laminate film thus obtained include a two-layer structure of a liquid crystal polyester film and a metal layer, a three-layer structure in which metal layers are laminated on both sides of a liquid crystal polyester film, and a five-layer structure in which liquid crystal polyester films and metal layers are alternately laminated. The laminate may be heat-treated as necessary for the purpose of developing high strength. The thickness of the metal layer is not particularly limited, but is preferably 1.5 to 1000 μm, more preferably 2 to 500 μm, even more preferably 5 to 150 μm, and particularly preferably 7 to 100 μm. If the thickness is thinner than this range, the mechanical strength is poor, and if the thickness is thicker than the above range, the handling and processability are poor.

[0049] The circuit board of the present invention includes at least one conductor layer and at least one insulator (or dielectric) layer, and the form is not particularly limited as long as the liquid crystal polyester film of the present invention is used as the insulator (or dielectric), and it can be used as various high-frequency circuit boards by known or conventional means. The circuit board may also be a circuit board (or a semiconductor element mounting board) on which a semiconductor element (e.g., an IC chip) is mounted.

[0050] The conductor layer used in the circuit board of the present invention is formed, for example, from at least a metal having electrical conductivity, and a circuit pattern is formed on this conductor layer by using a known circuit processing method. The conductor forming the conductor layer may be various metals having electrical conductivity, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof. In addition, a circuit pattern may be formed on the metal layer portion of the above-mentioned metal laminate film. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0052] The following resins were used in the examples and comparative examples. (Thermoplastic Liquid Crystal Polyester) LCP (1): A thermoplastic liquid crystal polyester consisting of a constitutional unit derived from p-hydroxybenzoic acid and a constitutional unit derived from 6-hydroxy-2-naphthoic acid (LAPEROS A950RX manufactured by Polyplastics Co., Ltd., melting point: 280°C, crystallization temperature: 235°C). LCP (2): Thermoplastic liquid crystal polyester consisting of a constitutional unit derived from p-hydroxybenzoic acid, a constitutional unit derived from 6-hydroxy-2-naphthoic acid, and a constitutional unit derived from terephthalic acid (LAPEROS C950RX manufactured by Polyplastics Co., Ltd., melting point: 320°C, crystallization temperature: 285°C). (amorphous polymer) Amorphous polymer (1): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX2001, manufactured by Eastman Chemical Company, Tg: 116°C) Amorphous polymer (2): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (Traitan TX1001, manufactured by Eastman Chemical Company, Tg: 108°C) Amorphous polymer (3): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from ethylene glycol (PCTG DN011, manufactured by Eastman Chemical Co., Tg: 90°C) Amorphous polymer (4): Amorphous copolyester containing a structural unit derived from terephthalic acid, a structural unit derived from 1,4-cyclohexanedimethanol, and a structural unit derived from isophthalic acid (PCTA AN004, manufactured by Eastman Chemical Company, Tg: 90°C) Amorphous polymer (5): Polyarylate resin (U-polymer U-100, manufactured by Unitika Ltd., Tg: 193°C) Amorphous polymer (6): Polysulfone resin (BASF Ultrason S3010, Tg: 187°C) (Additives) Polyester elastomer: Block copolymer of polybutylene terephthalate and polytetramethylene glycol (PBT / PTMG) The crystallization temperature was determined by using a differential scanning calorimeter (DSC) to completely melt the thermoplastic liquid crystal polyester by increasing the temperature from room temperature to 320-380°C at a rate of 10°C / min, and then decreasing the temperature to 30°C at a rate of 10°C / min. The crystallization temperature was determined as the apex of the exothermic peak. The glass transition temperature was determined using the value in the manufacturer's catalog.

[0053] (Manufacturing of film by inflation extrusion) After premixing the thermoplastic liquid crystal polyester and the like in the ratios shown in Table 1, the mixture was heated and kneaded in a single screw extruder, and melt extruded into bubbles from a circular inflation die (diameter 25 mm) at a discharge rate of 3 kg / h. The bubbles were stretched under conditions of draft ratio = 2 and blow ratio = 5, and a liquid crystal polyester film with a thickness of 50 μm was obtained by inflation extrusion molding. The resin temperature of the bubbles during film formation was controlled so that it was above the crystallization temperature from the contact position with the stabilizer to the pinch roll. The physical properties and appearance of the film obtained by the following evaluation methods are shown in Table 1.

[0054] (Physical properties: Dynamic friction coefficient) The measurement was performed by the following method with reference to JIS K7125-1999 using the measurement device shown in FIG. 1. FIG. 1 is a schematic diagram of the measurement device for the dynamic friction coefficient in the present invention. The measurement device shown in FIG. 1 includes a load cell 1 (Autograph AGS-500NX, manufactured by Shimadzu Corporation), a pulley 2, a sliding piece 3 (the bottom surface is covered with a fluorofiber woven fabric (manufactured by Toray Industries, Inc., model number: Toyoflon #406W), dimensions: length 63 mm x width 63 mm), a total mass 4 of the sliding piece (200 g = vertical load 1.96 N), a sample 5 (dimensions: length 80 mm x width 200 mm), and a hot plate (table) 6 with a temperature control function (manufactured by AS ONE, model number: CREAMIC HOTPLATE CHP-1700). The film obtained above was used as the sample, and it was cut into a rectangle so that the long side was parallel to the MD direction of the film, and the film was set so that the MD direction was parallel to the sliding direction. Then, the temperature of the hot plate was adjusted, and the slider 3 was moved relative to the sample 5 at a measurement speed of 100 mm / min to measure the dynamic friction coefficient between the surfaces of the slider 3 and the sample 5 at each temperature. The measurement was performed three times at each temperature, and the average value was taken as the dynamic friction coefficient. The coefficient of kinetic friction was calculated using the following formula: Kinetic friction force (F D ) was calculated as the average value for the first 6 cm after the start of the relative shear movement between the contact surfaces, ignoring the peak static friction force. μ D = F D / Fp μ D : Coefficient of kinetic friction F D :Dynamic friction force (N) Fp: Normal force generated by the mass of the sliding piece (=1.96N) (Physical properties: crystallization temperature) Using a differential scanning calorimeter (DSC), the film was heated from room temperature to 320-380°C at a heating rate of 10°C / min until the film was completely melted, and then cooled to 30°C at a cooling rate of 10°C / min, and the apex of the exothermic peak was measured as the crystallization temperature.

[0055] (Appearance: Wrinkles on film) The obtained film was visually inspected for slackness and wrinkles in the TD direction (horizontal wrinkles) and evaluated according to the following criteria. ○: No slack or wrinkles are observed in the film, or slight wrinkles are observed in the film △: The film has several faint and clear wrinkles and is loose. ×: Several clear wrinkles are observed on the film, and slack is observed.

[0056] [Table 1]

[0057] As shown in Table 1, the coefficient of kinetic friction (μ D1 ) is 0.25 or less, or the dynamic friction coefficient ratio (μ D1 / μ D2 The liquid crystal polyester films of Examples 1 to 7 having a value of 1.25 or less were excellent in mechanical properties, electrical properties, etc., and were smooth films free from slackness and wrinkles.

[0058] On the other hand, the coefficient of kinetic friction (μ D1 ) exceeds 0.25, or the dynamic friction coefficient ratio (μ D1 / μ D2 In the liquid crystal polyester films of Comparative Examples 1 to 3 in which the coefficient of kinetic friction was more than 1.25, slack and lateral wrinkles occurred in the film, and a smooth film could not be obtained. This result shows that it is important to reduce the dynamic friction coefficient near the crystallization temperature and to reduce the change in the dynamic friction coefficient near the crystallization temperature in order to obtain a smooth liquid crystal polyester film in which slack and wrinkles of the film are controlled in extrusion molding such as inflation extrusion molding. [Industrial Applicability]

[0059] As described above, the liquid crystal polyester film obtained by the present invention is used for electrical insulation of motors and transformers, element formation film of flexible solar cells, etc. by taking advantage of its excellent mechanical properties, electrical properties, dimensional stability, heat resistance, etc. It can also be used in the acoustic field, such as surface protection films and diaphragms. The metal laminate film of the present invention can also be used for circuit boards, capacitors, electromagnetic wave shielding materials, etc. The circuit board of the present invention may be used for various transmission lines and antennas (for example, microwave or millimeter wave antennas), and may also be used for antenna devices in which an antenna and a transmission line are integrated. [Explanation of symbols]

[0060] 1: Load cell 2: Pulley 3: Slider 4: Total mass of the sliding piece 5: Sample 6: Hot plate (table)

Claims

1. A liquid crystal polyester-based film containing a thermoplastic liquid crystal polyester as a main component, the film having a crystallization temperature (Tc) of 180° C. or more and 320° C. or less, and a dynamic friction coefficient (μ D1 ) is 0.25 or less.

2. A liquid crystal polyester-based film containing a thermoplastic liquid crystal polyester as a main component, the film having a crystallization temperature (Tc) of 180° C. or more and 320° C. or less, and a dynamic friction coefficient (μ D1 ) and the dynamic friction coefficient (μ D2 ) and the dynamic friction coefficient ratio (μ D1 / μ D2 ) is 1.25 or less.

3. The liquid crystal polyester according to claim 1 or 2, characterized in that the thermoplastic liquid crystal polyester contains at least one selected from the group consisting of a structural unit derived from p-hydroxybenzoic acid and a structural unit derived from 6-hydroxy-2-naphthoic acid.

4. 3. The liquid crystal polyester film according to claim 1, wherein the crystallization temperature (Tc) is 220° C. or higher and 300° C. or lower.

5. 3. The liquid crystal polyester film according to claim 1, comprising an amorphous copolyester having a glass transition temperature of 80° C. or more and 200° C. or less.

6. 6. The liquid crystal polyester film according to claim 5, wherein the amorphous copolyester contains a constituent unit derived from a terephthalic acid monomer and a constituent unit derived from 1,4-cyclohexanedimethanol.

7. 3. The liquid crystal polyester film according to claim 1, which is an inflation film.

8. 3. A metal laminate film, comprising the liquid crystal polyester film according to claim 1 or 2, and a metal layer laminated on one or both sides of the liquid crystal polyester film.

9. A circuit board comprising at least one conductor layer and the liquid crystal polyester film according to claim 1 or 2.

Citation Information

Patent Citations

  • Inflation molding method

    JP2001088213A

  • Inflation film forming method and apparatus therefor

    JP2002240146A